Skp2-dependent reactivation of AKT drives resistance to PI3K inhibitors - Clement, Emilie (Sci Signal, 2018)
The PI3K–AKT kinase signaling pathway is frequently deregulated in human cancers, particularly breast cancer where amplification and somatic mutations of the PIK3CA gene occur with high frequency in patients. Numerous small molecule inhibitors targeting both PI3K and AKT are under clinical evaluation, but dose-limiting toxicities and the emergence of resistance limit therapeutic efficacy. Various resistance mechanisms to PI3K inhibitors have been identified, including de novo mutations, feedback activation of the AKT or cross-talk pathways. Here, we found a previously unknown resistance mechanism to PI3K pathway inhibition that results in AKT rebound activation. In a subset of triple-negative breast cancer cell lines, treatment with PI3K inhibitor or depletion of PIK3CA expression ultimately promoted AKT reactivation in a manner dependent on the E3 ubiquitin ligase Skp2 but independent of PI3K activity or PIP(3) production. Resistance to PI3K inhibitors correlated with increased abundance of Skp2, ubiquitylation of AKT, cell proliferation in culture, and xenograft tumor growth in mice. The findings reveal a ubiquitin signaling feedback mechanism by which PI3K inhibitor resistance may emerge in aggressive breast cancer cells.